Implementation of the legislative oversight function on regional budget execution in Sidoarjo regency - Florencia, Serafin; Reviandani, Oktarizka (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2026)
This study analyzes the implementation of the legislative oversight function on the regional budget (APBD) in Sidoarjo Regency. It integrates Van Meter and Van Horn’s implementation model with Almond and Verba’s political culture theory to bridge the gap between formal regulations and actual bureaucratic behavior. Utilizing a qualitative interpretive case study design, research involved in-depth interviews with legislative members, regional auditors, and civil society activists. The findings reveal that while the Regional House of Representatives (DPRD) achieved high procedural compliance in policy standards and communication, oversight remains symbolic due to a deeply rooted 'subject' political culture that prioritizes institutional harmony over substantive evaluation. However, the study identifies a significant shift triggered by the rise of a 'participant' culture among the public, driven by digital transparency. This external pressure has evolved legislative disposition from a formal-bureaucratic mindset toward a responsive evaluative orientation, manifesting in increased field inspections and critical budget discussions. The study concludes that effective budget oversight depends not only on technical-administrative standards but is fundamentally determined by the transformation of political culture from an accommodative subject orientation toward a critical participant culture. This shift in social accountability serves as the primary catalyst for challenging elite political accommodation and ensuring the integrity of regional financial governance within a decentralized system.   Penelitian ini menganalisis implementasi fungsi pengawasan DPRD terhadap APBD di Kabupaten Sidoarjo melalui integrasi model Van Meter dan Van Horn dengan teori budaya politik Almond dan Verba. Menggunakan desain studi kasus interpretif kualitatif, penelitian ini melibatkan wawancara mendalam dengan anggota legislatif, auditor daerah, dan aktivis masyarakat sipil. Temuan mengungkapkan bahwa meskipun DPRD mencapai kepatuhan prosedural tinggi, kualitas pengawasan tetap bersifat simbolis akibat dominasi budaya politik 'subjek' yang memprioritaskan harmoni institusional di atas evaluasi substantif. Namun, studi ini mengidentifikasi pergeseran signifikan yang dipicu oleh bangkitnya budaya 'partisipan' masyarakat melalui transparansi digital. Tekanan eksternal ini mendorong evolusi disposisi legislatif dari pola pikir formal-birokratis menuju orientasi evaluatif yang responsif, yang bermanifestasi dalam peningkatan inspeksi lapangan dan pembahasan anggaran yang kritis. Penelitian menyimpulkan bahwa efektivitas pengawasan anggaran tidak hanya bergantung pada standar teknis-administratif, tetapi ditentukan oleh transformasi budaya politik dari orientasi 'subjek' yang akomodatif menuju budaya 'partisipan' yang kritis. Kekuatan mekanisme akuntabilitas sosial menjadi kunci untuk menantang akomodasi politik elit demi menjamin integritas tata kelola keuangan daerah dalam sistem desentralisasi.